(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
In this article we will talk about the semantic-grammatical features of the work” the fields left by my father". The head is explained by examples, focusing on the expression of the parts. The writer created a poetic style specific to the application of the head piece.